ANALISIS SISTEM PELAYANAN JASA WEDDING ORGANIZER DITINJAU DARI ETIKA BISNIS ISLAM (Studi Kasus Di UD. Santoso Wedding Organizer): Analysis Of Wedding Organizer Service System In Terms Of Islamic Business Ethics (Case Study In UD. Santoso Wedding Organizer) - Alwi Musa Muzaiyin (LP2M UIN KH.Achmad Siddiq Jember, 2021)
Wedding Organizer is a service that provide services for organizing all the activities relating to the need in a marriage. This business appears because of the opportunities of modern life who want speed, convenience, and practicality separately troubleshooting time deficiency urban communities. This research is motivated by the many people who use the wedding organizer to hold the wedding. Therefore, this study tried to see how the service system in UD. Santoso wedding organizer is already in line with Business Ethics Islam or not. From this background, the issue to be addressed is how the service system in UD. Santoso wedding organizer as well as whether the service system implemented by UD.Santoso it conforms with the Business Ethics Islam or not. The theory used in this study is one of them according to the